2015
DOI: 10.1098/rsob.150086
|View full text |Cite
|
Sign up to set email alerts
|

Recoverin depletion accelerates cone photoresponse recovery

Abstract: The neuronal Ca2+-binding protein Recoverin has been shown to regulate phototransduction termination in mammalian rods. Here we identify four recoverin genes in the zebrafish genome, rcv1a, rcv1b, rcv2a and rcv2b, and investigate their role in modulating the cone phototransduction cascade. While Recoverin-1b is only found in the adult retina, the other Recoverins are expressed throughout development in all four cone types, except Recoverin-1a, which is expressed only in rods and UV cones. Applying a double fla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3
1

Relationship

3
7

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 47 publications
4
38
0
Order By: Relevance
“…Even more strikingly, we found the UV-sensitive opsin 1 (cone pigments), short-wave-sensitive 1 (opn1sw1) to be expressed in bsx mutants, whereas it was not expressed in wild-type PGs in the larval stages. However, when we assessed the expression of rcv1a, which is specific to UV cones and rods (Zang et al, 2015), we observed a significant downregulation in bsx mutants. This result suggests that rod-like PhR cells are also affected in bsx mutants.…”
Section: Bsx Position In the Pineal Complex Transcriptional Networkmentioning
confidence: 79%
“…Even more strikingly, we found the UV-sensitive opsin 1 (cone pigments), short-wave-sensitive 1 (opn1sw1) to be expressed in bsx mutants, whereas it was not expressed in wild-type PGs in the larval stages. However, when we assessed the expression of rcv1a, which is specific to UV cones and rods (Zang et al, 2015), we observed a significant downregulation in bsx mutants. This result suggests that rod-like PhR cells are also affected in bsx mutants.…”
Section: Bsx Position In the Pineal Complex Transcriptional Networkmentioning
confidence: 79%
“…6g). Already the modulation of single gene products' relative expression levels could have a major effect, most notably in the case of transducin and GC3, and to a lesser extent also the downregulation of recoverin 2 (Rec2 (Dizhoor et al, 1991;Zang et al, 2015)) ( Fig. 6h).…”
Section: Differentialmentioning
confidence: 99%
“…The set of eye genes also included genes coding for proteins involved in the phototransduction cascade: RPE65, Arrestins, Recoverins, Transducins, PDE6, CNGA3 and CNGB3, GCAPs, zGCs, and GRKs. These genes code for a highly heterogeneous set of proteins with regard to their structure and functions (Imanishi, et al 2002; Wada, et al 2006; Schonthaler, et al 2007; Matveev, et al 2008; Nishiwaki, et al 2008; Rätscho, et al 2009; Renninger, et al 2011; Fries, et al 2013; Lagman, et al 2015; Zang, et al 2015; Lagman, et al 2016). Only genes whose expression was restricted to the retina and/or the pineal complex were retained.…”
Section: Methodsmentioning
confidence: 99%